Borowetan Sebuah Situs Di Wilayah Kerakaian Balitung - Baskoro Daru Tjahjono (Balai Arkeologi Yogyakarta, 2005)
The Borowetan site has only been exposed in a small part, which is a brick structure on the east side. So that through this data, it is very difficult to reveal its historical background, especially when it is related to the history of the ancient Mataram kingdom. Although this site is located close to the discovery of the Kayu Ara Hiwang inscription, it is still difficult to relate it to the inscription. In the inscription, it is mentioned that there is a sacred building complex (parhyangan) that must be cared for by the villagers of Kayu Ara Hiwang. However, the sacred building is located in Pariwutan. If it is true that Pariwutan is now Pulutan Village which is in Ngombol District - as said by MM Sukarto K. Atmodjo - it means that the brick structure is not part of a sacred building as mentioned in the Kayu Ara Hiwang inscription.